American horror story. Roanoke The complete sixth season [videorecording (DVD)]. - McDermott, Dylan; Peters, Evan, 1987-; Lady Gaga; Bates, Kathy, 1948-; Bassett, Angela (20th Century Fox, 2017)
Hoping to begin a new life in a North Carolina farmhouse, Shelby and Matt Miller flee Los Angeles only to find murder, mayhem and madness.